Effectiveness of Bos Funds Use in Improving Educational Facilities and Infrastructure - Tuti Lestari; Syarwani Ahmad; Wahid Ibrahim Banul Ngindom (Yayasan Sembilan Pemuda Indonesia, 2027)
This study analyzes the effectiveness of School Operational Assistance (BOS) fund utilization in improving educational facilities and infrastructure at SDN 27 Banyuasin I, identifies challenges encountered, and examines strategies implemented by the school to address them. A qualitative descriptive approach was employed, involving four purposively selected informants: the principal, two teachers, and one student. Data were collected through observation, semi-structured interviews, and documentation, with validity established through source and method triangulation. Analysis followed data reduction, presentation, conclusion drawing, and verification. BOS fund utilization was relatively effective in supporting facility provision and maintenance through needs-based planning, priority setting, classroom maintenance, minor repairs, and creating a conducive learning environment. However, effectiveness remains constrained by budget limitations, recurring maintenance requirements, evolving educational needs, and expenditure restrictions. The school addresses challenges through careful planning, prioritization, phased maintenance, community involvement, and periodic evaluation. This study provides contextualized evidence on BOS fund effectiveness in a rural elementary school setting, highlighting the interplay between budget constraints and managerial capacity. Findings emphasize that effective BOS utilization depends not only on budget availability but also on school managerial capacity to plan, implement, monitor, and evaluate fund use transparently and sustainably. This research contributes empirical insights for policymakers and school administrators, demonstrating that BOS funds primarily meet basic facility needs rather than financing large-scale development, offering actionable recommendations for optimizing resource allocation in similar contexts.